2017
DOI: 10.1111/joa.12743
|View full text |Cite
|
Sign up to set email alerts
|

3D analysis of sexual dimorphism in size, shape and breathing kinematics of human lungs

Abstract: Sexual dimorphism in the human respiratory system has been previously reported at the skeletal (cranial and thoracic) level, but also at the pulmonary level. Regarding lungs, foregoing studies have yielded sex-related differences in pulmonary size as well as lung shape details, but different methodological approaches have led to discrepant results on differences in respiratory patterns between males and females. The purpose of this study is to analyse sexual dimorphism in human lungs during forced respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 72 publications
(213 reference statements)
0
45
2
Order By: Relevance
“…Since abdominal breathing with diaphragmatic action is more predominant in males (Kaneko & Horie, ; Ragnarsdóttir & Kristinsdóttir, ; Verschakelen & Demedts, ), we can infer that the larger thoracic size increase of males and their large TLC are caused by differences in the ways that intercostal muscles and the diaphragm act to increase thoracic volume (the so‐called breathing pattern) between males and females. In this regard, recent research on human lungs (Torres‐Tamayo et al, ) observed that the base of the lungs, which largely tracks the diaphragmatic domes, undergoes a larger expansion in males than in females, also pointing to a larger diaphragmatic contribution to breathing kinematics in males than in females. However, it is important to note that differences in the kinematics of the diaphragmatic domes are not directly quantified by our measures of rib cage form and kinematics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since abdominal breathing with diaphragmatic action is more predominant in males (Kaneko & Horie, ; Ragnarsdóttir & Kristinsdóttir, ; Verschakelen & Demedts, ), we can infer that the larger thoracic size increase of males and their large TLC are caused by differences in the ways that intercostal muscles and the diaphragm act to increase thoracic volume (the so‐called breathing pattern) between males and females. In this regard, recent research on human lungs (Torres‐Tamayo et al, ) observed that the base of the lungs, which largely tracks the diaphragmatic domes, undergoes a larger expansion in males than in females, also pointing to a larger diaphragmatic contribution to breathing kinematics in males than in females. However, it is important to note that differences in the kinematics of the diaphragmatic domes are not directly quantified by our measures of rib cage form and kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in kinematic patterns were explored in a form space principal component analysis (form space PCA) (Mitteroecker, Gunz, Windhager, & Schaefer, ) and thorax shape differences associated with variations along the PC1‐2 axes were visualized using EVAN Toolkit (version 1.71; http://www.evan-society.org/). Kinematic differences were statistically tested by computing a dummy regression of shape on the kinematic state for each sex and calculating the angle between those regressions (Torres‐Tamayo et al, ), the significance being assessed via a permutation test ( N = 1,000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have used GM to assess sexual dimorphism, character displacement, craniofacial shape, and beyond in both extant and extinct species (Adams and Rohlf, ; Franklin et al, ; Kaliontzopoulou et al, ; Pierce et al, ) to attempt to discern relationships and/or evolutionary trends. No study at present has used these techniques to assess cervical spinal morphology and head/neck postures in humans, and the use of GM in biomechanical and/or kinematic analyses has been limited (but see Manfreda et al, ; Arlegi et al, ; Torres‐Tamayo et al, ). With such a drastic increase in handheld device usage in the past decade, further investigation into its effect on bone morphology is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual shape dimorphism and inter‐population shape variation of the lumbar vertebrae were both explored by carrying out a principal components analysis (PCA) in shape space (Mitteroecker et al, ; Zelditch et al, ). To determine statistically whether sex or inter‐population factors are associated with the shape variation of the lumbar spine explained by each principal component (PC), two dummy multivariate regressions of PC1 and PC2 shape variation were calculated (dummy variables: sex or population; 1,000 permutations, significance level 0.05) (Bastir et al, ; García‐Martínez et al, ; Monteiro, ; Rosas & Bastir, ; Torres‐Tamayo et al, ) using MorphoJ software (Klingenberg, ). Dummy (or indicator) variables are created to represent an attribute which may have an impact on the sample's variability (i.e., sex or population ) in a binary form (e.g., males = 1; females = −1) in order to identify which factor influences the shape variation summarized in each PC.…”
Section: Methodsmentioning
confidence: 99%